(untitled) (Research, Society and Development, 2021)
Objective: To analyze the scientific production in national and international journals regarding the Post Covid-19 syndrome, in the period 2019-2021. Guiding question: "What are the consequences of SARS-CoV-2 infection for the human body?" Methods: This is a state of the art regarding post-Covid syndrome, which was searched in the LILACS and Medline database with the terms “COVID-19”, “Coronavirus-19 disease”, “SARS-CoV-2 infections", "Coronavirus Infections", "Post COVID-19", in the 2019-2021 timeframe, with the inclusion criteria: article available in full and is published in Portuguese, English and Spanish. 16 articles were selected. Outcomes: Tackling SARS-CoV-2 goes beyond tackling an unknown virus, which results in the development of an equally unknown disease, but which is leading us to confront our own limitations as human beings, imperfect and limited. Thus, physical sequelae appear in people who have overcome COVID-19. Conclusion: It is not always the person assisted in serious condition who presents significant impairments in the post-illness, remaining after recovery from the infection with some persistent type of sequel. Post-COVID syndrome represents a clinical picture that results from the repercussion of the disease in the body and is composed of a set of nonspecific symptoms. As it is something recent, not much is known about it, but what is clear is that it does not only affect people who developed the severe form of COVID-19 and who were hospitalized in the ICU for a long period.